THE QUALITY OF EDUCATION IS THE MOST IMPORTANT FACTOR FOR IMPROVING THE DEVELOPMENT OF THE NEW UZBEKISTAN - Mamayusupova Dildoraxon (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
We need to create our bright future with quality education which gives us numerous opportunities. Because talented young people are the founder of the country's bright future.